Viral IFN-Regulatory factors inhibit activation-induced cell death via two positive regulatory IFN-regulatory factor 1-dependent domains in the CD95 ligand Promoter - Kirchhoff, Sabine; Li-Weber, Min; Krammer, Peter H. (The journal of immunology, 2002)
The CD95 (also called APO-1/Fas) system plays a major role in the induction of apoptosis in lymphoid and nonlymphoid tissues. The CD95 ligand (CD95L) is induced in response to a variety of signals, including IFN-γ and TCR/CD3 stimulation. Here we report the identification of two positive regulatory IFN-regulatory factor-dependent domains (PRIDDs) in the CD95L promoter and its 5′ untranslated region, respectively. EMSAs demonstrate specific binding of IFN-γ-induced IFN-regulatory factor 1 (IRF-1) to the PRIDD sequences. Ectopic IRF-1 expression induces CD95L promoter activity. Furthermore, we demonstrate that PRIDDs play an important role in TCR/CD3-mediated CD95L induction. Most interestingly, viral IRFs of human herpes virus 8 (HHV8) totally abolish IRF-1-mediated and strongly reduce TCR/CD3-mediated CD95L induction. We demonstrate here for the first time that viral IRFs inhibit activation-induced cell death. Thus, these results demonstrate an important mechanism of HHV8 to modulate the immune response by down-regulation of CD95L expression. Inhibition of CD95-dependent T cell function might contribute to the immune escape of HHV8.